Chữ Việt trong xử lí truyền thông - Việt, Ngô Trung (Journal of Computer Science and Cybernetics, 2016)
In this paper, the relation between representing of Vietnamese characters, computer processing and communication,  concerning with the Vietnamese standard code, will be discussed. Two architectures for representing  Vietnamese characters: Precomposed and  separated are presented. Based on that, some arguments about setting up a Vietnamese standard code for processing and communication are discussed. This standard code proposal consists of three separated code tables but  unified in the  same  framework and  satisfied all requirements about Vietnamese characters in computer processing and communication.